Pansitopenia dan Hipoglikemia – Presentasi Atipikal dari Tirotoksikosis - Ridha Amalia; Ade E Y Nasution; Nanny N M Soetedjo (Universitas Kristen Maranatha, 2022)
Pancytopenia and hypoglycemia are atypical presentations and potentially devastating complications of thyrotoxicosis which may lead to delayed diagnosis. This case report aims to describe atypical presentations of thyrotoxicosis. A case report of a 55-year-old man who was admitted with a history of epigastric pain for seven days, accompanied by malaise, weight loss, clammy hand, increase in appetite followed by a decrease in appetite, diarrhea, nausea, nervousness, and restlessness, palpitation, easy fatigability, and fever which happened for the past one month until the day he was admitted on 13 October 2020 to Sumedang General Hospital. He was treated accordingly. Laboratory examination showed pancytopenia, hypoglycemia, and low Thyroid Stimulating Hormone level. The Electrocardiogram showed atrial fibrillation and left ventricular strain. The patient was diagnosed with Thyroid Crisis. After four days of treatment, the clinical condition of the patient was getting better. Conclusion, history taking of previous symptoms and disease is becoming significant to establish a working diagnosis. A thorough history taking could help a physician to consider hyperthyroidism as a differential diagnosis not merely based on laboratory results. Recognition of unusual thyrotoxicosis presentations is important in early diagnosis and effective treatment of the disease to prevent further complication and morbidity.